Implementation Knowledge Management in Management Thesis for High Education in Indonesia - Setiyani, Lila; Gintings, Abdorrakhman; Syamsudin, Abin; Arifin, Daeng (Rekayasa, 2020)
Management thesis in high education  have some lackness in knowledge management. Every busines process that happen in management thesis don’t have efective approach to integrate data workflow and to acuisition the knowledge. Therefore, knowledge management  system for management thesis  that suit with high education are needed. This paper gives suggestions about new architecture software that offer service for management thesis in high education to make business process more efective and efficien. Methodology that is used for development new software uses model process software development life cycle(SDLC) with web platform , that will increase collaboration in business process management thesis. The result of this implementation can increased efective and eficiency business process management thesis significantly.